Acute Generalized Exanthematous Pustulosis (AGEP) Unveiled: A Tertiary Hospital Case Series on Antibiotic-Induced Adverse Drug Reactions in Davao City, Philippines - Doria, Irson Thurs; Ang, Maria Carmen; Orcasitas, Jessie (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Acute generalized exanthematous pustulosis (AGEP) is a rare and severe cutaneous adverse reaction (SCAR) characterized by the rapid onset of widespread small sterile pustules on erythematous skin. It is only estimated to occur in 1 to 5 cases per million annually worldwide. It is distinguishable from other SCARs based on the time interval between drug intake and the onset of symptoms. This characteristic time interval is a key factor in differentiating AGEP from other skin reactions. This case series presents three distinct cases of AGEP in patients admitted to a tertiary hospital in Davao City, Philippines. Our cases demonstrate the diverse clinical presentations and triggers of AGEP, primarily involving antibiotics, including ceftriaxone, piperacillin-tazobactam, clindamycin, and amoxicillin. The three cases share similarities in demographic profiles, with patients being female in the 26 to 60 age group; however, they exhibit variations in the onset of symptoms relative to drug exposure, notably appearing 1 day, 4 days, and 24 days following antibiotic use. All patients had no mucosal and organ involvement. Treatment strategies of our patients involved identification and discontinuation of the offending medication, application of topical steroids, and providing supportive care. All three patients had resolution of the skin lesions. Because AGEP exhibits a distinctive and rapidly evolving clinical presentation, it is primarily diagnosed based on clinical findings. All three patients presented rapid eruption of multiple, small, non-follicular pustules on a background of an erythematous exanthem following drug exposure. The most commonly implicated agents causing AGEP include antibiotics. Beta-lactams are the main offenders in this case series. This case series underscores the importance of recognizing AGEP as a potential adverse reaction to antibiotics and the need for prompt identification, withdrawal of the offending medication, and timely initiation of treatment to ensure favorable outcomes.